Reinvestigating a key site for Polynesian prehistory: new results from the Hane dune site, Ua Huka (Marquesas). Issue 3 (3rd June 2014) - Conte, Eric; Molle, Guillaume
Abstract Since the first excavations by Sinoto and Kellum in 1964–1965, the Hane dune site, situated on Ua Huka, Marquesas Islands, has been considered as a key site in central Eastern Polynesia and, as such, has been utilised in different colonisation models. However, some problems remained, particularly due to the lack of full publication of the original excavation results, and it appeared that these issues could only be resolved with new investigations. In 2009, the authors opened an 18 m2 excavation that produced a controlled stratigraphy of ten layers. This paper presents the first results, focusing on the stratigraphy and new dates obtained, indicating a sequence of nearly six centuries, from early human settlement around the mid‐tenth century until the abandonment of the dune around the mid‐sixteenth century.